A psycho-social approach to consumer ethics. (May 2021) - Chatzidakis, Andreas; Shaw, Deirdre; Allen, Matthew
Research into consumer ethics has grown considerably over the last two decades. However, most studies adopt either a psychological or a socio-cultural approach and there has been little in the way of bridging the two together. Accordingly, we draw on Kleinian psychoanalysis as a means of advancing an explicitly psycho-social understanding of consumer ethics. Following an emerging tradition that conceptualizes moral dilemmas as questions of care, rather than abstract principles of moral and environmental justice, we conceptualize consumer care as a capacity that for its extension across difference and distance is subject to a variety of biographical, inter-subjective and institutional-level processes. Subsequently, we attempt to redress forms of theoretical reductionism noted in both psychological and socio-cultural accounts of everyday morality in consumption. We corroborate a more nuanced, mid-ground conceptualization that neither precludes nor overstates the possibility of consumer agency while also locating agency in inanimate objects. Finally, we offer a methodological contribution by introducing a psychoanalytic (Kleinian) approach to analyzing textual and visual data.